Exploring the Preferences of Prospective Students in Choosing Private Higher Education Institutions - Putri, Nanda Alifia (Journal of Emerging Business Management and Entrepreneurship Studies, 2025)
As competition among private higher education institutions (PHEIs) in Indonesia intensifies, understanding student preferences becomes essential for developing effective marketing strategies and admission policies. This study investigates the key factors influencing high school students' decisions when choosing higher education institutions in Indonesia, and how these preferences differ between public and private school students. Utilizing the Consumer Decision-Making Process (CDMP) framework, the research employs a qualitative approach. Data was gathered through focus group discussions with nine (9) public school students and in-depth interviews with six (6) private school students from the Jabodetabek area. The findings indicate that public school students prioritize institutional reputation and affordability. In contrast, private school students emphasize program fit and opportunities for personal growth. These results highlight the need for private higher education institutions to tailor their marketing and admission strategies to effectively attract diverse student segments and enhance recruitment outcomes.